13 NHSBT Tissue and eye services: the role of the hospital development nurse practitioner. (16th November 2022) - Winstanley, Emma; Jones, Marion; Mander, Gail; Cooke, Caroline; Partridge, Elizabeth
Abstract : NHS Blood and Transplant (NHSBT) Tissue and Eye Services (TES) save and improve the lives of thousands of patients every year. The roles and responsibilities of the nurses working in TES are diverse. Across the TES supply chain nursing roles are pivotal. They range from raising awareness of tissue donation and creating robust referral systems through to skilled communication with recently bereaved families over the telephone, as well as advanced nursing practice in clinical decision-making regarding suitability for transplantation and research. In the UK, around 25 million people have registered to donate organs and tissues. However, there is poor understanding around the tissue-donation process. Hospital development nurse practitioners (HDNPs) provide a professional link between service Providers/users and TES so that effective working partnerships can be developed. HDNPs ensure that there is a professional link from TES to support, educate and advise a wide range of health professionals about tissue donation. They are a visible and respected presence in the areas within which they work and continuously build on these successful working partnerships and contractual agreements to increase donor referrals. Consistent findings from a global body of research for organs and tissues over the past 15 years shows that there are key factors that influence family decision making (Sque et al, 2008; Siminoff et al, 2010; Long-Sutehall et al, 2012; Sque et al, 2018). Evidence suggests that key factors include: Failure by health professionals to recognise potential donors Reluctance of health professionals to talk about tissue donation Family/next of kin not agreeing to donation due to concerns about the donation process (for example, the post donation appearance of the donor) or personally held views. The role of the HDNP aims to overcome some of these barriers and work towards increasing the number of referrals of potential tissue donors. This includes creating robust referral systems, raising awareness, educating, and sharing information about tissue donation so that patients and their families can make an informed choice about donating tissue for transplant and/or research. HDNPs work closely with selected NHS trusts at strategic levels to implement referral systems. This includes working alongside senior colleagues such as chief executives, directors of nursing, end-of-life-care specialists and coroners. HDNPs work closely with selected trusts in developing automatic referral systems whereby 100% of adult deaths are referred so nurses are able to reach many more families to discuss the option of donating tissue.